Examining the effects of rational emotive behavior therapy (REBT) on performance outcomes in elite paralympic athletes - Wood, A. G.; Barker, J. B.; Turner, M.; Sheffield, D. (Scandinavian Journal of Medicine & Science in Sports, 2018)
Traditionally a psychotherapeutic intervention, Rational Emotive Behavior Therapy (REBT) is receiving increasing attention within the extant literature as an intervention to enhance the athletic performance and psychological wellbeing of competitive athletes. Whilst the benefits of REBT on psychological health are established, less is understood about the effects on athletic performance. The present study aimed to examine the immediate and maintained effects of REBT on physiological, psychological, and performance outcomes with elite Paralympic athletes. Using a single-case research design, eight athletes recruited from the same Paralympic sport (M = 40.12, SD = 12.99) received five, one-to-one REBT sessions. Measures of irrational beliefs were collected weekly, whereas the remaining psychological and physiological measures were collected at a pre-, post-, and at a 9-month follow-up time-point. Visual and statistical analysis of the data indicates reductions in irrational beliefs were coupled with reductions in Systolic Blood Pressure (SBP) indicative of an adaptive physiological response, improved athletic performance during competition simulations, and reductions in avoidance goals. Furthermore, social validation data indicated greater self-awareness, emotional control, and enhanced focus during competition as a result of the REBT intervention. This study contributes to growing literature supporting the efficacy of REBT as an intervention that not only facilitates psychological health but also enhances athletic performance. Results are discussed with reference to theory, limitations, and future recommendations.